2012
DOI: 10.1111/j.1447-0756.2011.01721.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of twin pregnancies after amniocentesis

Abstract: Our cohort showed a low fetal loss rate after amniocentesis for uncomplicated twin pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 31 publications
0
18
1
Order By: Relevance
“…Other studies have reported a very low rate of fetal loss following amniocentesis in twin pregnancies. For example, Kan and colleagues in Hong Kong reported in 2012 that out of 105 twin pregnancies, 102 gave birth to live babies (Kan, Lee, Leung, Chan, Tang, & Chan, 2012). However, in some other studies, the results have been reported to be inconsistent with the present study, and contrary to our findings, amniocentesis has increased the rate of fetal loss in patients.…”
Section: Discussioncontrasting
confidence: 99%
“…Other studies have reported a very low rate of fetal loss following amniocentesis in twin pregnancies. For example, Kan and colleagues in Hong Kong reported in 2012 that out of 105 twin pregnancies, 102 gave birth to live babies (Kan, Lee, Leung, Chan, Tang, & Chan, 2012). However, in some other studies, the results have been reported to be inconsistent with the present study, and contrary to our findings, amniocentesis has increased the rate of fetal loss in patients.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the accuracy of ultrasound detection declines dramatically due to thinner chorionicity in the second trimester [8]. Invasive approaches such as amniocentesis or cord blood sampling combined with microsatellite DNA markers could also detect zygosity with high accuracies, but it presents a potential miscarriage at a risk of 0.5–1% [9]. Thus there is a huge demand for a noninvasive method to accurately determine the zygosity type without the limitation of gestational age.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing frequencies of multiple pregnancies and advanced maternal age have expanded the need for invasive prenatal diagnosis 123415. Fetal loss after invasive prenatal diagnostic tests is one of the major concerns of pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…These women who conceive a multiple pregnancy with ART are usually of more advanced maternal age. With increased age-related chromosomal abnormalities and the risk of aneuploidy per gestation in dizygotic twins, an increasing need is seen for prenatal diagnosis in multiple pregnancies 1345…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation